Genetic parameters for Kleiber ratio and its relation to other body weight traits in Nilagiri and Sandyno sheep - VENKATARAMANAN, R; SUBRAMANIAN, A; SIVASELVAM, S N; SIVAKUMAR, T; SREEKUMAR, C (The Indian Journal of Animal Sciences, 2016)
Kleiber ratio (KR) is an indicator of growth efficiency irrespective of body size. The trait was recommended as an efficient indirect selection criterion. The present study was done to estimate genetic parameters for KR and explore the possibility of its use as a selection criterion in Nilagiri and Sandyno sheep. KR for the pre-weaning (birth to 3-months) and post-weaning (3– 6, 6–9, 9–12 and 3–12 months) periods was studied. Pre-weaning KR was much higher than post-weaning KR in both the breeds. The mean pre-weaning KR for Nilagiri and Sandyno sheep was 14.37 and 14.52, respectively. All the post-weaning KR values were less than six. Animal model including or ignoring maternal effects was used to obtain REML estimates of (co)variances. The best model was chosen based on log-likelihood ratio test. Maternal effects and inbreeding were not significant for KR at any of the age intervals. Moderate estimates of heritability were obtained for pre-weaning KR in both the breeds. Among the post-weaning KR, the age interval from 3–6 months and 3–12 months showed moderate values in Nilagiri sheep. Post-weaning KR for Sandyno sheep showed negligible to low heritability estimates. The maximum heritability of 0.143 was for KR 3–6 months in Nilagiri sheep. In Nilagiri sheep, genetic correlation between pre-weaning KR and body weight traits ranged from 0.634 to 0.875. Similarly, in Sandyno sheep, the values ranged from 0.883 to 0.959. Thus pre-weaning KR could be used as a criterion for indirect selection to improve important body weight traits.